Carbon nanotube composite aggregate wire, heat-treated body of carbon nanotube composite aggregate wire, method for producing carbon nanotube composite aggregate wire, and method for producing heat-treated body of carbon nanotube composite aggregate wire

By forming an amorphous carbon layer on the surface of carbon nanotubes and then heat-treating it, the problems of carbon nanotubes being difficult to elongate and process were solved, achieving the vertical aggregation of highly crystalline carbon nanotubes and improving their conductivity, making them suitable for applications such as automotive engines.

CN112672976BActive Publication Date: 2025-01-10SUMITOMO ELECTRIC INDUSTRIES LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN201980057578.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-09-03
Filing Date
2019-08-29
Publication Date
2025-01-10
Estimated Expiration
2039-08-29

AI Technical Summary

Technical Problem

Existing technologies struggle to effectively extend and process highly crystalline carbon nanotubes, especially due to their small diameter and high crystallinity, which makes it difficult for them to align and aggregate along the longitudinal direction, thus affecting their application in fields such as electrical wires.

Method used

By forming a layer containing amorphous carbon on the surface of carbon nanotubes and heat-treating it under specific conditions, carbon nanotube composite aggregate lines are formed. Subsequently, the amorphous carbon layer is removed to obtain highly crystalline carbon nanotube composite aggregate lines.

Benefits of technology

Multiple highly crystalline carbon nanotubes were oriented and aggregated along the longitudinal direction, which improved the processability and conductivity of the carbon nanotube composite, making it suitable for applications such as automotive engines.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112672976B_ABST
    Figure CN112672976B_ABST
Patent Text Reader

Abstract

The carbon nanotube composite assembly line is a carbon nanotube composite assembly line including a plurality of carbon nanotube composites, wherein each of the plurality of carbon nanotube composites includes a carbon nanotube and a layer containing amorphous carbon covering each carbon nanotube, and the carbon nanotube has a D / G ratio of no more than 0.1, the D / G ratio being a ratio of the peak intensity of the D band to the peak intensity of the G band in Raman spectroscopy analysis at a wavelength of 532 nm. Each of the plurality of carbon nanotube composites is fibrous and has a diameter of 0.1 μm to 50 μm, and the plurality of carbon nanotube composites are oriented along the longitudinal direction of the carbon nanotube composite assembly line.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a carbon nanotube composite wire, a heat-treated body of a carbon nanotube composite wire, a method for manufacturing a carbon nanotube composite wire, and a method for manufacturing a heat-treated body of a carbon nanotube composite wire. This application claims priority to Japanese Patent Application No. 2018-164909 filed on September 3, 2018, the entire contents of which are incorporated herein by reference. Background Art

[0002] Carbon nanotubes, which are cylindrical sheets made of carbon atoms bonded in a hexagonal pattern, are a material with excellent properties, such as one-fifth the weight of copper, 20 times the strength of steel, and conductivity similar to that of metal. Therefore, electric wires using carbon nanotubes are expected to contribute to the lightweighting and miniaturization of (particularly) automobile engines and improve corrosion resistance.

[0003] For example, as described in Patent Document 1 (Japanese Patent Laid-Open No. 2005-330175), carbon nanotubes are obtained by a vapor phase growth method in which a raw material gas containing carbon is supplied while heating a fine catalyst such as iron to grow carbon nanotubes from the catalyst.

[0004] Reference List

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Laid-Open No. 2005-330175 Summary of the invention

[0007] [1] According to one aspect of the present disclosure, the carbon nanotube composite assembly line is

[0008] A carbon nanotube composite assembly line including a plurality of carbon nanotube composites,

[0009] The plurality of carbon nanotube composites each include a carbon nanotube and a layer containing amorphous carbon covering the carbon nanotube.

[0010] The D / G ratio of the carbon nanotubes is 0.1 or less. The D / G ratio is the ratio of the peak intensity of the D band to the peak intensity of the G band in Raman spectroscopy analysis at a wavelength of 532 nm.

[0011] Each of the plurality of carbon nanotube composites is in a fiber shape and has a diameter of 0.1 μm or more and 50 μm or less.

[0012] The plurality of carbon nanotube composites are oriented along the longitudinal direction of the carbon nanotube composite assembly line.

[0013] [2] The heat-treated body of the carbon nanotube composite wire assembly according to one aspect of the present disclosure is

[0014] A heat-treated body of the carbon nanotube composite wire assembly described in [1] above.

[0015] [3] According to one aspect of the present disclosure, a method for manufacturing a carbon nanotube composite aggregate wire is

[0016] A method for manufacturing a carbon nanotube composite assembly line, the method comprising:

[0017] A first step of preparing a plurality of carbon nanotubes;

[0018] a second step of obtaining a plurality of carbon nanotube composites by coating each of the plurality of carbon nanotubes with a layer containing amorphous carbon; and

[0019] The third step is to align and aggregate a plurality of carbon nanotube composites in the longitudinal direction thereof to obtain a carbon nanotube composite aggregate line.

[0020] [4] According to one aspect of the present disclosure, a method for manufacturing a heat-treated body of a carbon nanotube composite wire assembly is as follows:

[0021] A method for manufacturing a heat-treated body of a carbon nanotube composite wire assembly, the method comprising:

[0022] A first step of preparing a plurality of carbon nanotubes;

[0023] a second step of obtaining a plurality of carbon nanotube composites by coating each of the plurality of carbon nanotubes with a layer containing amorphous carbon;

[0024] a third step of obtaining a carbon nanotube composite aggregate line by aligning and aggregating a plurality of carbon nanotube composites along their longitudinal direction; and

[0025] A fourth step is to obtain a heat-treated body of the carbon nanotube composite wire assembly by heat-treating the carbon nanotube composite wire assembly to remove the layer containing amorphous carbon. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 FIG. 1 is a diagram showing a typical exemplary configuration of a carbon nanotube composite aggregate wire according to an embodiment of the present disclosure.

[0027] Figure 2 is an optical micrograph of a carbon nanotube composite assembly line according to one embodiment of the present disclosure.

[0028] Figure 3 : is a diagram showing a typical exemplary configuration of a carbon nanotube composite used in one embodiment of the present disclosure.

[0029] Figure 4 is intercepted along the straight line XX Figure 3 Cross-sectional view of a carbon nanotube composite.

[0030] Figure 5 is a graph showing a typical Raman spectrum of carbon nanotubes.

[0031] Figure 6 FIG. 1 is a diagram showing a Raman imaging image of the G band of a heat-treated body of a carbon nanotube composite wire assembly according to an embodiment of the present disclosure.

[0032] Figure 7 FIG. 1 is a diagram showing a Raman imaging image of a D band of a heat-treated body of a carbon nanotube composite wire assembly according to an embodiment of the present disclosure.

[0033] Figure 8 is a diagram showing an example of a carbon nanotube production apparatus.

[0034] Fig. 9 is a diagram showing an example of carbon nanotubes used in one embodiment of the present disclosure. DETAILED DESCRIPTION

[0035] [Problems to be Solved by the Present Disclosure]

[0036] The diameter of carbon nanotubes obtained by the current technology of making carbon nanotubes is about 0.4nm to 20nm, and the maximum length is about 550mm. In order to use carbon nanotubes as electric wires, longer carbon nanotubes are required, so research is being conducted on technologies that can extend carbon nanotubes.

[0037] As one method of extending carbon nanotubes, a method of arranging and collecting a plurality of carbon nanotubes in a longitudinal direction to obtain a collection line is conceivable.

[0038] However, as described above, since each carbon nanotube is extremely small, with a diameter of about 0.4 nm to 20 nm, it is impossible to observe the carbon nanotube with an optical microscope. In particular, the higher the crystallinity of the carbon nanotube, the smaller the diameter of the carbon nanotube, and its handling becomes more difficult. Therefore, it is difficult to align and aggregate a plurality of carbon nanotubes along their longitudinal direction to obtain an aggregate line.

[0039] Therefore, the purpose of the present disclosure is to provide a carbon nanotube composite aggregate wire, a heat-treated body of a carbon nanotube composite aggregate wire, a method for manufacturing a carbon nanotube composite aggregate wire, and a method for manufacturing a heat-treated body of a carbon nanotube composite aggregate wire, which are capable of obtaining a heat-treated body of a carbon nanotube composite comprising a plurality of highly crystalline carbon nanotubes oriented and assembled along their longitudinal direction.

[0040] [Advantageous Effects of the Present Disclosure]

[0041] According to the above aspect, there can be provided a heat-treated body of a carbon nanotube composite including a plurality of highly crystalline carbon nanotubes oriented and assembled in the longitudinal direction thereof.

[0042] [Description of Embodiments of the Present Disclosure]

[0043] First, various aspects of the present disclosure will be described one by one.

[0044] (1) The carbon nanotube composite assembly line according to one aspect of the present disclosure is

[0045] A carbon nanotube composite assembly line including a plurality of carbon nanotube composites,

[0046] The plurality of carbon nanotube composites each include a carbon nanotube and a layer containing amorphous carbon covering the carbon nanotube.

[0047] The D / G ratio of the carbon nanotubes is 0.1 or less. The D / G ratio is the ratio of the peak intensity of the D band to the peak intensity of the G band in Raman spectroscopy analysis at a wavelength of 532 nm.

[0048] Each of the plurality of carbon nanotube composites is in a fiber shape and has a diameter of 0.1 μm or more and 50 μm or less.

[0049] The plurality of carbon nanotube composites are oriented along the longitudinal direction of the carbon nanotube composite assembly line.

[0050] According to the carbon nanotube composite assembly line, a heat-treated carbon nanotube composite body including a plurality of highly crystalline carbon nanotubes aligned and assembled in the longitudinal direction thereof can be obtained.

[0051] (2) Preferably, the layer containing amorphous carbon has a D / G ratio of 0.5 or more, which is the ratio of the peak intensity of the D band to the peak intensity of the G band in Raman spectroscopy at a wavelength of 532 nm. Thus, only the layer containing amorphous carbon can be removed by heat treatment.

[0052] (3) The heat-treated body of the carbon nanotube composite wire assembly according to one aspect of the present disclosure is

[0053] A heat-treated body of the carbon nanotube composite wire assembly as described in (1) or (2) above.

[0054] The heat-treated body of the formed carbon nanotube composite wire assembly includes a plurality of highly crystalline carbon nanotubes aligned and assembled in the longitudinal direction thereof.

[0055] (4) According to one aspect of the present disclosure, a method for manufacturing a carbon nanotube composite assembly line is as follows:

[0056] A method for manufacturing a carbon nanotube composite assembly line, the method comprising:

[0057] A first step of preparing a plurality of carbon nanotubes;

[0058] a second step of obtaining a plurality of carbon nanotube composites by coating each of the plurality of carbon nanotubes with a layer containing amorphous carbon; and

[0059] The third step is to align and aggregate a plurality of carbon nanotube composites in the longitudinal direction thereof to obtain a carbon nanotube composite aggregate line.

[0060] According to this production method, a carbon nanotube composite that is easy to handle is produced, and the carbon nanotube composite is used to produce a carbon nanotube composite aggregate wire. Therefore, a carbon nanotube composite aggregate wire can be easily obtained.

[0061] (5) Preferably, the carbon nanotube has a D / G ratio of 0.1 or less, where the D / G ratio is the ratio of the peak intensity of the D band to the peak intensity of the G band in Raman spectroscopy at a wavelength of 532 nm, and

[0062] Each of the plurality of carbon nanotube composites is in a fiber shape and has a diameter of 0.1 μm to 50 μm.

[0063] Thereby, the carbon nanotube composite aggregate wire can include highly crystalline carbon nanotubes, and the handling property can be improved.

[0064] (6) Preferably, the second step includes heat-treating the plurality of carbon nanotubes in a hydrocarbon gas at a temperature of 950° C. to 1100° C. In this way, a layer containing amorphous carbon having a predetermined D / G ratio can be formed on the surface of each carbon nanotube while maintaining the crystallinity of the carbon nanotubes.

[0065] (7) Preferably, the third step includes

[0066] The third step (a) is to obtain a carbon nanotube composite dispersion by dispersing a plurality of carbon nanotube composites in a solvent,

[0067] a third step (b) of orienting a plurality of carbon nanotube composites in a specific direction by causing the carbon nanotube composite dispersion to flow in a specific direction, and

[0068] After the third step (b), the solvent in the carbon nanotube composite dispersion is removed to obtain a carbon nanotube composite aggregate wire.

[0069] Thereby, a plurality of carbon nanotube composites can be effectively aligned and assembled in the longitudinal direction thereof.

[0070] (8) According to one aspect of the present disclosure, a method for manufacturing a heat-treated body of a carbon nanotube composite wire assembly is as follows:

[0071] A method for manufacturing a heat-treated body of a carbon nanotube composite wire assembly, the method comprising:

[0072] A first step of preparing a plurality of carbon nanotubes;

[0073] a second step of obtaining a plurality of carbon nanotube composites by coating each of the plurality of carbon nanotubes with a layer containing amorphous carbon;

[0074] a third step of obtaining a carbon nanotube composite aggregate line by aligning and aggregating a plurality of carbon nanotube composites along their longitudinal direction; and

[0075] The fourth step is to obtain a heat-treated body of the carbon nanotube composite wire assembly by heat-treating the carbon nanotube composite wire assembly to remove the layer containing amorphous carbon.

[0076] According to the manufacturing method, a carbon nanotube composite that is easy to handle is prepared, the carbon nanotube composite is used to prepare a carbon nanotube composite wire, and the carbon nanotube composite wire is heat-treated to obtain a heat-treated carbon nanotube composite wire.

[0077] (9) Preferably, the carbon nanotube has a D / G ratio of 0.1 or less, where the D / G ratio is the ratio of the peak intensity of the D band to the peak intensity of the G band in Raman spectroscopy at a wavelength of 532 nm, and

[0078] Each of the plurality of carbon nanotube composites is in a fiber shape and has a diameter of 0.1 μm to 50 μm.

[0079] Therefore, the carbon nanotube composite can include highly crystalline carbon nanotubes, and the handling property can be improved. In addition, the carbon nanotube composite aggregate wire can also include highly crystalline carbon nanotubes.

[0080] (10) When the diameter of the carbon nanotube composite wire assembly is P1, and the diameter of the heat-treated body of the carbon nanotube composite wire assembly is P2, P1 and P2 preferably exhibit a relationship represented by the following formula 1:

[0081] 100≤P1 / P2≤10000 Formula 1.

[0082] In the heat-treated body of the carbon nanotube composite wire assembly, since the carbon nanotubes are in contact or bonded to each other, the heat-treated body of the carbon nanotube composite wire assembly has excellent electrical conductivity.

[0083] (11) Preferably, the second step includes heat-treating the plurality of carbon nanotubes in a hydrocarbon gas at a temperature of 950° C. to 1100° C. In this way, a layer containing amorphous carbon having a predetermined D / G ratio can be formed on the surface of each carbon nanotube while maintaining the crystallinity of the carbon nanotubes.

[0084] (12) Preferably, the third step includes

[0085] The third step (a) is to obtain a carbon nanotube composite dispersion by dispersing a plurality of carbon nanotube composites in a solvent,

[0086] a third step (b) of orienting a plurality of carbon nanotube composites in a specific direction by causing the carbon nanotube composite dispersion to flow in a specific direction, and

[0087] After the third step (b), the solvent in the carbon nanotube composite dispersion is removed to obtain a carbon nanotube composite aggregate wire.

[0088] Thereby, a plurality of carbon nanotube composites can be effectively aligned and assembled in the longitudinal direction thereof.

[0089] (13) Preferably, the heat treatment in the fourth step includes heat treating the carbon nanotube composite wire assembly at a temperature of 400° C. to 800° C. under an oxidizing condition.

[0090] This makes it possible to remove only the layer containing amorphous carbon in the carbon nanotube composite while maintaining the crystallinity of the carbon nanotubes.

[0091] (14) Preferably, the heat treatment in the fourth step includes heat treating the carbon nanotube composite wire assembly at a temperature of 560° C. to 690° C. under an oxidizing condition.

[0092] This makes it possible to remove only the layer containing amorphous carbon in the carbon nanotube composite while maintaining the crystallinity of the carbon nanotubes.

[0093] [Details of the embodiments of the present disclosure]

[0094] Specific examples of a carbon nanotube composite wire assembly, a heat-treated body of a carbon nanotube composite wire assembly, a method for manufacturing a carbon nanotube composite wire assembly, and a method for manufacturing a heat-treated body of a carbon nanotube composite wire assembly according to an embodiment of the present disclosure will be described below with reference to the accompanying drawings.

[0095] In the drawings of the present disclosure, the same reference numerals represent the same or corresponding components. In addition, in order to make the drawings clear and simple, the dimensional relationships of length, width, thickness, depth, etc. are appropriately changed and do not necessarily represent the actual dimensional relationships.

[0096] [First embodiment: Carbon nanotube composite assembly line]

[0097] (Carbon Nanotube Composite Wire)

[0098] like Figure 1 and Figure 2 As shown, the carbon nanotube composite wire (hereinafter also referred to as CNT composite wire) 10 according to the present embodiment includes a plurality of carbon nanotube composites 1 (hereinafter also referred to as CNT composites). Figure 3 and 4 As shown, each of the plurality of carbon nanotube composites 1 includes a carbon nanotube 2 and a layer 3 containing amorphous carbon covering the carbon nanotube 2. The D / G ratio of the carbon nanotube 2 is less than 0.1, and the D / G ratio is the ratio of the peak intensity of the D band to the peak intensity of the G band in Raman spectroscopy analysis at a wavelength of 532 nm. Each of the plurality of carbon nanotube composites 1 is fibrous and has a diameter of not less than 0.1 μm and not more than 50 μm. The plurality of carbon nanotube composites 1 are oriented along the longitudinal direction of the carbon nanotube composite aggregate line 10. Through these features, the carbon nanotube composite aggregate line according to the present embodiment can have the effects shown in (1) to (3) below.

[0099] (1) The carbon nanotube composite assembly line according to the present embodiment includes a plurality of carbon nanotube composites, and the plurality of carbon nanotube composites are oriented along the longitudinal direction of the carbon nanotube composite assembly line. Here, the expression "a plurality of carbon nanotube composites are oriented along the longitudinal direction of the carbon nanotube composite assembly line" means that the longitudinal direction of the carbon nanotube composite assembly line and the longitudinal direction of the carbon nanotube composite extend in substantially the same direction. That is, the carbon nanotube composite assembly line is formed by orienting and assembling a plurality of carbon nanotube composites in their longitudinal directions. It should be noted that the expression "substantially the same direction" means that the maximum angle formed between two different carbon nanotube composites included in the carbon nanotube composite assembly line is less than 10°.

[0100] Each of the plurality of carbon nanotube composites includes highly crystalline carbon nanotubes having a D / G ratio of 0.1 or less. Therefore, in the carbon nanotube composite wire according to the present embodiment, the plurality of highly crystalline carbon nanotubes are also oriented in the longitudinal direction of the carbon nanotube composite wire.

[0101] By performing heat treatment, the layer containing amorphous carbon included in each carbon nanotube composite can be removed, thereby obtaining purified carbon nanotubes having only high crystallinity. In this specification, carbon nanotubes obtained by removing the layer containing amorphous carbon in the carbon nanotube composite are also referred to as purified carbon nanotubes.

[0102] Therefore, by heat treating the carbon nanotube composite aggregate wire according to the present embodiment, it is possible to obtain a heat-treated body of the carbon nanotube composite aggregate wire which includes a plurality of highly crystalline refined carbon nanotubes, and in which the plurality of highly crystalline refined carbon nanotubes are oriented and assembled along their longitudinal direction (hereinafter also referred to as the heat-treated body of the CNT composite aggregate wire).

[0103] (2) As described in (1) above, since in the heat-treated body of the CNT composite wire, a plurality of highly crystalline refined carbon nanotubes are oriented and assembled along the longitudinal direction thereof, the heat-treated body of the CNT composite wire can have high tensile strength and high electrical conductivity. Therefore, using the carbon nanotube composite wire according to this embodiment, a heat-treated body of the CNT composite wire having high tensile strength and high electrical conductivity can be obtained.

[0104] (3) Since the plurality of carbon nanotube composites used in the carbon nanotube composite aggregate wire according to the present embodiment are each fibrous and have a diameter of 0.1 μm to 50 μm, they can be observed with an optical microscope and can be easily handled. Therefore, the carbon nanotube composite aggregate wire including the carbon nanotube composites can also be observed with an optical microscope and can be easily handled.

[0105] The carbon nanotube composite assembly line is in a linear shape, in which a plurality of fibrous carbon nanotube composites are oriented and assembled along the longitudinal direction thereof. The expression "a plurality of fibrous carbon nanotube composites are oriented and assembled along the longitudinal direction thereof" means that a plurality of fibrous carbon nanotube composites are assembled in such a manner that the longitudinal directions of the respective plurality of carbon nanotube composites extend along substantially the same direction. It should be noted that the expression "substantially the same direction" means that the maximum angle formed between two different carbon nanotube composites included in the carbon nanotube composite assembly line is 10° or less.

[0106] The overall appearance of the carbon nanotube composite aggregate wire is not particularly limited, and may have any appearance depending on the purpose. For example, the carbon nanotube composite aggregate wire may be in a straight line shape or a curved line shape.

[0107] The length of the carbon nanotube composite assembly line is not particularly limited and can be appropriately adjusted according to the purpose. For example, the length of the CNT composite assembly line is preferably 10 μm or more, more preferably 100 μm or more, and further preferably 1000 μm or more. In particular, when the length of the CNT composite assembly line is 1000 μm or more, it is easy to place the CNT composite assembly line in an arbitrary area by manipulating the manipulator, which is suitable from the perspective of making (for example) a micro-electromechanical system (MEMS). Although the upper limit of the length of the CNT composite assembly line is not particularly limited, it is preferably 600 mm or less from the perspective of manufacturing. The length of the CNT composite assembly line can be measured by observation with an optical microscope or the naked eye. When the CNT composite assembly line is in a curved shape rather than a straight shape, the length along the curve is measured.

[0108] The size of the diameter of the carbon nanotube composite assembly wire is not particularly limited and can be appropriately adjusted according to the purpose. For example, the diameter of the CNT composite assembly wire is preferably greater than 10 μm, and more preferably greater than 100 μm. In particular, when the diameter of the CNT composite assembly wire is greater than 100 μm, it is easy to place the CNT composite assembly wire in an arbitrary area by manipulating the manipulator, which is suitable from the perspective of making (for example) a micro-electromechanical system (MEMS). Although the upper limit value of the diameter of the CNT composite assembly wire is not particularly limited, it is preferably less than 1 mm from the perspective of manufacturing. In the present embodiment, the size of the diameter of the CNT composite assembly wire is smaller than the length of the CNT composite assembly wire.

[0109] In this specification, the diameter of a carbon nanotube composite assembly line refers to the average outer diameter of a CNT composite assembly line. The average outer diameter of a CNT composite assembly line is obtained by observing the cross-sections of two arbitrary positions of a CNT composite assembly line with an optical microscope, measuring the outer diameter in each cross-section and calculating the average value of the obtained outer diameters, wherein the outer diameter is the distance between the two farthest points on the periphery of the CNT composite assembly line.

[0110] In the carbon nanotube composite assembly line, it is only necessary to aggregate a plurality of CNT composites to form a CNT composite assembly line in the form of a single line. For a plurality of CNT composites, it is only necessary that at least some of the CNT composites are in physical contact with each other. Therefore, all CNT composites may be in physical contact with each other, or there may be CNT composites that are not in contact with each other.

[0111] (Carbon Nanotube Composite)

[0112] Each carbon nanotube composite includes a carbon nanotube (hereinafter also referred to as CNT) and a layer containing amorphous carbon covering the carbon nanotube. The D / G ratio of the carbon nanotube is less than 0.1, and the D / G ratio is the ratio of the peak intensity of the D band to the peak intensity of the G band in Raman spectroscopy analysis with a wavelength of 532 nm. The carbon nanotube composite is fibrous, and the diameter R is greater than or equal to 0.1 μm and less than or equal to 50 μm.

[0113] The carbon nanotube composite is in the shape of a single fiber. The overall appearance of the carbon nanotube composite can be in a straight line shape, or in a curved shape, such as a U shape.

[0114] The length of the carbon nanotube complex can be appropriately adjusted according to the purpose. For example, the length of the CNT complex is preferably 10 μm or more, and more preferably 100 μm or more. In particular, when the length of the CNT complex is 100 μm or more, this length is suitable from the viewpoint of making a CNT complex assembly line. Although the upper limit of the length of the CNT complex is not particularly limited, it is preferably 600 mm or less from the viewpoint of manufacturing. The length of the CNT complex can be measured by observation with an optical microscope. When the CNT complex is in a curved shape rather than a straight line, the length along the curve is measured.

[0115] The diameter of the carbon nanotube composite is 0.1 μm to 50 μm. Thus, the CNT composite can be observed with an optical microscope and is easy to handle. The diameter of the CNT composite is preferably 0.1 μm to 5 μm, and more preferably 0.5 μm to 3 μm.

[0116] In this specification, the diameter of a carbon nanotube composite refers to the average outer diameter of a CNT composite. The average outer diameter of a CNT composite is obtained by observing two cross sections of a CNT composite at arbitrary positions with an optical microscope, measuring the outer diameter in each cross section and calculating the average value of the outer diameters obtained, wherein the outer diameter is the distance between the two farthest points on the periphery of the CNT composite.

[0117] (Carbon Nanotubes)

[0118] There is no limitation on the structure of the carbon nanotube as long as the carbon nanotube has a D / G ratio of 0.1 or less, which is the ratio of the peak intensity of the D band to the peak intensity of the G band in Raman spectroscopy analysis at a wavelength of 532 nm. Examples of carbon nanotubes that can be used include single-layer carbon nanotubes having only a single carbon layer (graphene) in a cylindrical shape, double-layer carbon nanotubes or multi-layer carbon nanotubes having a stack of multiple carbon layers in a cylindrical shape, and stacked cup-shaped nanotubes having a structure in which graphene is stacked in a bottomless paper cup shape.

[0119] The shape of the carbon nanotube is not particularly limited, and both the carbon nanotube with closed end and the carbon nanotube with open end can be used. The catalyst used in the production process of the carbon nanotube can be attached to one or both ends of the carbon nanotube. In addition, a tapered portion made of tapered graphene can be formed at one or both ends of the carbon nanotube.

[0120] The length of the carbon nanotube can be appropriately selected according to the purpose. For example, the length of the carbon nanotube is preferably 10 μm or more, and more preferably 100 μm or more. In particular, when the length of the carbon nanotube is 100 μm or more, this length is suitable from the viewpoint of making a CNT composite assembly line. Although the upper limit of the length of the carbon nanotube is not particularly limited, it is preferably 600 mm or less from the viewpoint of manufacturing. The length of the CNT can be measured by observation with a scanning electron microscope.

[0121] The diameter of the carbon nanotube is preferably 0.6 nm to 20 nm, and more preferably 1 nm to 10 nm. In particular, when the diameter of the carbon nanotube is 1 nm to 10 nm, such a diameter is suitable from the viewpoint of heat resistance under oxidative conditions.

[0122] In this specification, the diameter of a carbon nanotube refers to the average outer diameter of a CNT. The average outer diameter of a CNT can be calculated by directly observing the projection image of the CNT with a transmission electron microscope and measuring it. Alternatively, the average outer diameter of a CNT can be obtained by measuring the Raman shift value in the radial breathing mode unique to the CNT using Raman spectroscopy and calculating it from the relationship between the diameter of the CNT and the Raman shift value. When the CNT includes a tapered portion at one or both ends thereof, the measurement is performed at a position other than the tapered portion.

[0123] The D / G ratio of the carbon nanotube is 0.1 or less, and the D / G ratio is the ratio of the peak intensity of the D band to the peak intensity of the G band in Raman spectroscopy analysis at a wavelength of 532 nm. The D / G ratio will be described using the Raman spectrum of the carbon nanotube obtained by Raman spectroscopy analysis.

[0124] The G band is a band at 1590 cm-1 in the Raman spectrum obtained by Raman spectroscopy. -1 The D band is a peak derived from CNTs seen near the Raman shift of 1350 cm-1 in the Raman spectrum obtained by Raman spectroscopy. -1 The peaks derived from amorphous carbon or graphite or defects in CNTs are seen near the Raman shift of . Therefore, the smaller the value of the D / G ratio, the higher the crystallinity of the carbon nanotubes, and the less the content of amorphous carbon or defective graphite in the carbon nanotubes.

[0125] The D / G ratio of each CNT included in the CNT composite assembly wire according to the present embodiment is less than 0.1, the content of amorphous carbon or defective graphite is small, and the crystallinity is high. Therefore, the CNT can have high tensile strength and high conductivity. If the D / G ratio of the CNT exceeds 0.1, the CNT may not have sufficient tensile strength and high conductivity. In addition, if the D / G ratio of the CNT exceeds 0.1, then in the method for manufacturing the heat-treated body of the carbon nanotube composite assembly wire of the fourth embodiment described below, when the layer containing amorphous carbon in each CNT composite is removed, the CNT itself may deteriorate. The D / G ratio is preferably less than 0.1, and more preferably less than 0.01. Although the lower limit of the D / G ratio is not particularly limited, it may be (for example) above 0.

[0126] In this specification, the D / G ratio of each carbon nanotube in the carbon nanotube composite aggregate wire is a value measured by the following method.

[0127] First, the carbon nanotube composite assembly wire is heat-treated at a temperature of 650°C in the atmosphere for 60 minutes. Thus, the layer containing amorphous carbon in the carbon nanotube composite assembly wire is removed, thereby obtaining a heat-treated body of the carbon nanotube composite assembly wire. Raman spectroscopy analysis is performed on the heat-treated body of the carbon nanotube composite assembly wire under the following conditions to obtain a Raman spectrum (hereinafter also referred to as the Raman spectrum of the heat-treated body of the CNT composite assembly wire). The D / G ratio is calculated from the peak intensity of the D band and the peak intensity of the G band in the Raman spectrum of the heat-treated body of the CNT composite assembly wire. The D / G ratio of the heat-treated body of the CNT composite assembly wire is regarded as the D / G ratio of each carbon nanotube in the carbon nanotube composite assembly wire.

[0128] Raman spectroscopy analysis conditions

[0129] Wavelength: 532nm

[0130] Laser power: 17mW

[0131] Exposure time: one second

[0132] Average number of times: three times

[0133] Objective lens magnification: 50 times

[0134] The reason why the D / G ratio of each CNT in the CNT composite aggregate wire according to the present embodiment is considered to be the same as the D / G ratio of the heat-treated body of the CNT composite aggregate wire is as follows.

[0135] Before coating the plurality of carbon nanotubes with a layer containing amorphous carbon, the inventors performed Raman spectroscopy analysis on each of the plurality of carbon nanotubes under the same conditions as above to obtain a Raman spectrum (hereinafter also referred to as a CNT Raman spectrum). The D / G ratio was calculated from the peak intensity of the D band and the peak intensity of the G band of each of the plurality of CNT Raman spectra obtained.

[0136] Then, each carbon nanotube is coated with a layer containing amorphous carbon to prepare a CNT composite. A plurality of CNT composites are oriented and assembled along their longitudinal direction to obtain a carbon nanotube composite aggregate line. The CNT composite aggregate line is heat-treated at a temperature of 650°C for 60 minutes to remove the layer containing amorphous carbon in the CNT composite aggregate line to obtain a heat-treated body of the CNT composite aggregate line. Raman spectroscopy is performed on the heat-treated body of the CNT composite aggregate line under the above conditions to obtain a Raman spectrum (hereinafter also referred to as the Raman spectrum of the heat-treated body of the CNT composite aggregate line). The D / G ratio is calculated from the peak intensity of the D band and the peak intensity of the G band in the Raman spectrum of the heat-treated body of the CNT composite aggregate line.

[0137] It can be confirmed that the value obtained by averaging the data of the D / G ratio of a plurality of carbon nanotubes before being coated with the layer containing amorphous carbon calculated above is substantially the same as the value of the D / G ratio of the heat-treated body of the CNT composite aggregate obtained by removing the layer containing amorphous carbon in the CNT composite aggregate. This indicates that the D / G ratio of the carbon nanotubes before being coated with the layer containing amorphous carbon is maintained in the CNTs of the CNT composite aggregate and the CNTs of the heat-treated body of the CNT composite aggregate. Therefore, in this specification, the D / G ratio of each carbon nanotube in the CNT composite aggregate can be regarded as the same as the D / G ratio of the heat-treated body of the CNT composite aggregate.

[0138] It should be noted that when the carbon nanotube composite collective line was subjected to Raman spectroscopy analysis (wavelength: 532 nm) to obtain a Raman spectrum, a peak of the D band was clearly confirmed. The D band is considered to originate from a layer containing amorphous carbon included in the CNT composite collective line.

[0139] The method for producing carbon nanotubes is not particularly limited as long as it is a method that can obtain carbon nanotubes that satisfy the above-mentioned D / G ratio. Examples of such methods include thermal decomposition methods, in which a raw material gas such as an alcohol-based or hydrocarbon-based raw material gas is thermally decomposed in a heating furnace by using catalyst particles having a nanometer-scale diameter, so that carbon crystals grow on the catalyst particles, and carbon nanotubes are obtained. Examples of thermal decomposition methods include: a method in which catalyst particles are supported on a substrate by coating, etc., so that CNTs grow on catalyst particles; a method in which a catalyst is suspended in a gas phase so that CNTs grow on a catalyst; and a method in which a plurality of catalyst particles in a close contact state are separated in a raw material gas flow so that CNTs grow between a plurality of catalyst particles.

[0140] (Layer containing amorphous carbon)

[0141] The layer containing amorphous carbon is a layer (region) containing amorphous carbon. There is no particular limitation on amorphous carbon, and conventionally known amorphous carbon can be used. Examples of usable amorphous carbon include ta-C (tetrahedral amorphous carbon), aC (amorphous carbon), ta-C:H (hydrogenated tetrahedral amorphous carbon) and aC:H (hydrogenated amorphous carbon). In particular, aC is preferably used because a layer containing amorphous carbon can be formed by a simple technique. For example, amorphous carbon having a ratio of SP3 / SP2 of 0.2 or more and 0.8 or less can be used.

[0142] The D / G ratio of the layer containing amorphous carbon is preferably greater than 0.5, and the D / G ratio is the ratio of the peak intensity of the D band to the peak intensity of the G band in the Raman spectroscopy analysis with a wavelength of 532nm. Thus, only the layer containing amorphous carbon can be removed by heat treatment. The D / G ratio of the layer containing amorphous carbon is more preferably greater than 0.7, and further preferably greater than 1.0. Although there is no particular restriction on the upper limit of the D / G ratio of the layer containing amorphous carbon, it is preferably (for example) less than 2.0. Here, the D / G ratio of the layer containing amorphous carbon can be regarded as the same as the D / G ratio of each carbon nanotube composite. This is because the volume ratio of CNT in the CNT composite is 10 -7 % by volume or less, which is extremely small, and therefore it is considered that the influence of the D / G ratio of CNTs on the D / G ratio of the CNT composite is negligible.

[0143] Since the conditions of the Raman spectroscopic analysis performed to calculate the D / G ratio of the layer containing amorphous carbon are the same as the conditions of the Raman spectroscopic analysis performed to calculate the D / G ratio of the above-mentioned carbon nanotubes, the description thereof will not be repeated.

[0144] The content of amorphous carbon in the layer containing amorphous carbon is preferably 1% by volume or more, more preferably 10% by volume or more, and further preferably 50% by volume or more. Although the upper limit of the content of amorphous carbon in the layer containing amorphous carbon is not particularly limited, it may be, for example, 100% by volume. The content of amorphous carbon in the layer containing amorphous carbon may be measured by thermogravimetric analysis.

[0145] The layer containing amorphous carbon may be made of amorphous carbon alone, or may contain graphite crystallites, tar, and an organic compound generated by thermal decomposition in addition to amorphous carbon.

[0146] Graphite crystallites refer to crystal particles composed of graphite having a volume average particle size of 1 nm or more and 50 nm or less. In this specification, "volume average particle size" refers to the median particle size (d50) in the volume-based particle size distribution (volume distribution), and refers to the average particle size of all graphite crystallites contained in the layer containing amorphous carbon. It should be noted that in this specification, "volume average particle size" may be simply referred to as "particle size".

[0147] The particle size of each graphite crystallite used to calculate the particle size (volume average particle size) of the graphite crystallite can be measured by the following method. First, a reflected electron image of a layer containing amorphous carbon at any region in any cross section of the CNT complex is observed with an electron microscope at a magnification of 5000 times. Then, in the reflected electron image, the diameter of the circumscribed circle of the particles constituting each graphite crystallite (i.e., the circumscribed circle equivalent diameter) is measured, and the diameter is determined as the particle size of the graphite crystallite.

[0148] Based on the particle diameters of the graphite crystallites obtained above, the volume average particle diameter was calculated.

[0149] The content of graphite crystallites in the layer containing amorphous carbon is preferably 99% by volume or less, more preferably 90% by volume or less, and further preferably 50% by volume or less. Although the lower limit of the content of graphite crystallites in the layer containing amorphous carbon is not particularly limited, it may be, for example, 1% by volume. The content of graphite crystallites in the layer containing amorphous carbon may be measured by observation with a transmission electron microscope or by thermogravimetric analysis.

[0150] The thickness of the layer containing amorphous carbon is preferably 0.05 μm to 25 μm. Here, the thickness of the layer containing amorphous carbon refers to the average value of the shortest distances extending from an arbitrary point on the periphery of the CNT to an arbitrary point on the periphery of the CNT complex in the cross section of the CNT complex. Therefore, since the carbon nanotube complex has a sufficient diameter, the CNT complex is easy to handle. The thickness of the layer containing amorphous carbon is more preferably 0.05 μm to 2.5 μm, and further preferably 0.25 μm to 1.5 μm. The thickness of the layer containing amorphous carbon is obtained by observing the cross section at two arbitrary positions of the CNT complex with an electron microscope to measure the thickness of the layer containing amorphous carbon, and calculating the average value of the obtained thickness.

[0151] [Second embodiment: Heat-treated carbon nanotube composite wire assembly]

[0152] The heat-treated body of the carbon nanotube composite wire assembly according to the present embodiment is a heat-treated body obtained by heat-treating the carbon nanotube composite wire assembly according to the first embodiment described above.

[0153] The amorphous carbon layer included in the carbon nanotube composite constituting the carbon nanotube composite assembly line can be removed by heat treatment. Therefore, the heat-treated body of the carbon nanotube composite assembly line includes a plurality of refined carbon nanotubes obtained by removing the amorphous carbon layer in the plurality of carbon nanotube composites, and the plurality of refined carbon nanotubes are oriented and assembled along the longitudinal direction of the heat-treated body of the CNT composite assembly line.

[0154] Reference Figure 6 and Figure 7 A method for confirming that a heat-treated body of a carbon nanotube composite assembly line includes a plurality of purified carbon nanotubes and does not include a layer containing amorphous carbon is described. Figure 6 This is a G-band Raman imaging image of the heat-treated body of the carbon nanotube composite wire assembly according to the present embodiment. Figure 7 is with Figure 6 Raman imaging image of the D band of the heat-treated body of the same carbon nanotube composite line.

[0155] Raman spectroscopy analysis was performed on the heat-treated carbon nanotube composite wire assembly under the same conditions as in the first embodiment to obtain a Raman imaging image of the G band (see Figure 6 ) and D-band Raman imaging images (see Figure 7 ). Using an inVia Raman microscope manufactured by Renishaw and WiRE software, Raman spectra were measured at intervals of 1 μm by a point imaging method to obtain each Raman imaging image.

[0156] exist Figure 6 and 7 In FIG. 1 , the portion surrounded by a thick line at the center shows a two-dimensional profile of the G band / D band intensity of the heat-treated body of the carbon nanotube composite wire assembly placed on the quartz substrate. The two-dimensional profile is obtained by binarizing each Raman imaging image to minimize the influence of the background.

[0157] exist Figure 6 In the Raman imaging image of the G band shown, the light-colored portion indicates that the peak intensity of the G band is high, the dark-colored portion indicates that the peak intensity of the G band is low, and in particular, the black portion indicates that the G band is not detected. Here, the G band is a peak derived from CNTs. Therefore, in Figure 6 , it can be confirmed that a plurality of highly crystalline purified carbon nanotubes exist in the portion surrounded by the dotted line. It should be noted that the presence of a plurality of purified carbon nanotubes can be confirmed by observing that the size of the light-colored portion is sufficiently larger than the size of one CNT.

[0158] On the other hand, in the Raman imaging image of the D band, the light-colored portion indicates that the peak intensity of the D band is high, the dark-colored portion indicates that the peak intensity of the D band is low, and in particular, the black portion indicates that the D band is not detected. Here, the D band is a peak derived from defects in graphite or amorphous carbon. Therefore, in Figure 7 It can be confirmed that in Figure 6 There are no graphite defects or amorphous carbon at the same positions as the portions surrounded by the dotted lines.

[0159] That is, from Figure 6 and 7 It was confirmed that in the portion surrounded by the dotted line, purified carbon nanotubes with high crystallinity existed, and a layer containing amorphous carbon did not exist.

[0160] As described above, by generating G-band Raman imaging images and D-band Raman imaging images of the heat-treated body of the carbon nanotube composite aggregate line and analyzing these Raman imaging images, it can be confirmed that the heat-treated body of the carbon nanotube composite aggregate line includes multiple refined carbon nanotubes and does not include a layer containing amorphous carbon.

[0161] The heat-treated body of the carbon nanotube composite wire assembly is in the shape of a line in which a plurality of refined carbon nanotubes are oriented and assembled along the longitudinal direction thereof. The overall appearance of the heat-treated body of the carbon nanotube composite wire assembly is not particularly limited and may be any appearance according to the purpose. For example, the appearance may be in a straight line shape or a curved line shape.

[0162] The length of the heat-treated body of the carbon nanotube composite assembly wire is not particularly limited and can be appropriately adjusted according to the purpose. For example, the length of the heat-treated body of the CNT composite assembly wire is preferably 10 μm or more, more preferably 100 μm or more, and further preferably 1000 μm or more. In particular, when the length of the heat-treated body of the CNT composite assembly wire is 1000 μm or more, it is easy to make a long linear CNT strand by twisting a plurality of heat-treated bodies of the CNT composite assembly wire. In addition, the heat-treated body of the CNT composite assembly wire is conducive to placing the CNT composite assembly wire in an arbitrary area by manipulating the manipulator, which is suitable for making micro-electromechanical systems (MEMS) (for example). Although the upper limit of the length of the heat-treated body of the CNT composite assembly wire is not particularly limited, it is preferably 600 mm or less from the manufacturing point of view. The length of the heat-treated body of the CNT composite assembly wire can be measured by optical microscope observation or visual observation. When the heat-treated body of the CNT composite assembly wire is in a curved shape rather than a straight shape, the length along the curve is measured.

[0163] The size of the diameter of the heat-treated body of the carbon nanotube composite collective wire is not particularly limited, and can be appropriately adjusted according to the purpose. For example, the diameter of the heat-treated body of the CNT composite collective wire is preferably 0.01 μm or more, and more preferably 1 μm or more. In particular, when the diameter of the heat-treated body of the CNT composite collective wire is 1 μm or more, it is easy to make CNT strands. Although the upper limit of the diameter of the heat-treated body of the CNT composite collective wire is not particularly limited, it is preferably 10 μm or less from the viewpoint of manufacturing.

[0164] In this specification, the diameter of the heat-treated body of the CNT composite wire assembly refers to the average outer diameter of the heat-treated body of the CNT composite wire assembly. The average outer diameter of the heat-treated body of the CNT composite wire assembly is obtained by observing the cross-sections at two arbitrary positions of the heat-treated body of the CNT composite wire assembly with a scanning electron microscope, measuring the outer diameters in each cross-section and calculating the average value of the obtained outer diameters, wherein the outer diameter is the distance between the two farthest points on the periphery of the heat-treated body of the CNT composite wire assembly.

[0165] The D / G ratio of the heat-treated body of the carbon nanotube composite assembly wire is preferably 0.1 or less, and the D / G ratio is the ratio of the peak intensity of the D band to the peak intensity of the G band in the Raman spectrum analysis with a wavelength of 532nm. Thus, the heat-treated body of the carbon nanotube composite assembly wire can have high crystallinity. Therefore, the heat-treated body of the carbon nanotube composite assembly wire can have high tensile strength and high conductivity. The D / G ratio is preferably 0.01 or less. Although the lower limit of the D / G ratio is not particularly limited, it can be (for example) 0.001 or more.

[0166] Since the conditions for Raman spectroscopic analysis for calculating the D / G ratio of the heat-treated body of the carbon nanotube composite aggregate wire are the same as those for calculating the D / G ratio of CNTs described in the first embodiment, the description thereof will not be repeated.

[0167] [Third Embodiment: Method for Producing Carbon Nanotube Composite Aggregate Wire]

[0168] The method for manufacturing a carbon nanotube composite aggregate wire according to the present embodiment includes: a first step of preparing a plurality of carbon nanotubes; a second step of obtaining a plurality of carbon nanotube composites by coating each of the plurality of carbon nanotubes with a layer containing amorphous carbon; and a third step of obtaining a carbon nanotube composite aggregate wire by orienting and aggregating the plurality of carbon nanotube composites along their longitudinal direction.

[0169] (First step)

[0170] In the first step, a plurality of carbon nanotubes are prepared. Each carbon nanotube may be the same as the carbon nanotube described in the first embodiment.

[0171] The method for preparing each carbon nanotube is not particularly limited, and commercially available carbon nanotubes may be used, or carbon nanotubes produced by a conventionally known method may be used. In particular, it is preferable to prepare carbon nanotubes produced by a method in which a plurality of catalyst particles in a close contact state are separated in a raw material gas stream so that CNTs grow between the plurality of catalyst particles (hereinafter, this method is also referred to as a floating bridge (FB (floating bridge)) method), because carbon nanotubes having high crystallinity and consisting only of six-membered rings are obtained.

[0172] For example, you can use Figure 8 The carbon nanotube manufacturing apparatus 20 shown implements the FB method. The carbon nanotube manufacturing apparatus 20 includes: a tubular reaction chamber 21, a gas supply mechanism 22 for supplying a carbon-containing gas into the reaction chamber 21 from one end of the reaction chamber 21, a catalyst supply mechanism 23 for releasing a plurality of catalyst particles P in a contact state into the carbon-containing gas flowing through the reaction chamber 21, and a substrate holding mechanism 24 placed in the reaction chamber 21 for holding a substrate B for capturing the catalyst particles P.

[0173] <Reaction Room>

[0174] The reaction chamber 21 stratifies the carbon-containing gas flow in an inlet region 25 located upstream of the catalyst supply mechanism 23 , and forms carbon nanotubes in a formation region 26 located downstream of the catalyst supply mechanism 23 using the stratified carbon-containing gas.

[0175] The reaction chamber 21 is provided with a heater 27 . In other words, the reaction chamber 21 is heated by the heater 27 .

[0176] The internal temperature of formation region 26 of reaction chamber 21 is preferably 800° C. to 1200° C. To maintain such a temperature, the carbon-containing gas may be heated and then supplied to reaction chamber 21 by gas supply mechanism 22 , or may be heated in inlet region 25 .

[0177] <Gas Supply Mechanism>

[0178] The gas supply mechanism 22 may include a gas tank 28 and a flow control valve 29 to supply the carbon-containing gas to the reaction chamber 21 .

[0179] A reducing gas such as a hydrocarbon gas is used as the carbon-containing gas supplied by the gas supply mechanism 22. As such a carbon-containing gas, for example, a mixed gas of acetylene and nitrogen or argon, methane, or the like can be used.

[0180] The lower limit of the average flow rate of the carbon-containing gas supplied from the gas supply mechanism 22 into the reaction chamber is 0.05 m / sec, preferably 0.10 cm / sec, and more preferably 0.20 cm / sec. On the other hand, the upper limit of the average flow rate of the carbon-containing gas in the reaction chamber 21 is preferably 10.0 cm / sec, and more preferably 0.5 cm / sec. If the average flow rate of the carbon-containing gas in the reaction chamber 21 is less than the lower limit, the wind pressure may not be sufficient to extend the carbon nanotubes formed between the catalyst particles P. On the contrary, if the average flow rate of the carbon-containing gas in the reaction chamber 21 is greater than the upper limit, the carbon nanotubes may be separated from the catalyst particles P, which may stop the growth of the carbon nanotubes and thus hinder the formation of the carbon nanotubes.

[0181] The lower limit of the Reynolds number of the carbon-containing gas flow supplied by the gas supply mechanism 22 to the reaction chamber 21 is preferably 0.01, and more preferably 0.05. On the other hand, the upper limit of the above-mentioned Reynolds number is 1000, preferably 100, and more preferably 10. If the Reynolds number is less than the lower limit, the design may be excessively restricted, which may make the carbon nanotube production apparatus 20 unnecessarily expensive and may unnecessarily reduce the production efficiency of carbon nanotubes. If the Reynolds number is greater than the upper limit, the carbon-containing gas flow may be disturbed, which may hinder the generation of carbon nanotubes between the catalyst particles P and the extension of the carbon nanotubes.

[0182] Preferably, the gas supply mechanism 22 can repeatedly change the amount of carbon-containing gas supplied to the reaction chamber 21. Thus, the flow rate of the carbon-containing gas in the reaction chamber 21 increases or decreases, which promotes the separation of multiple integrated catalyst particles, thereby increasing the number of carbon nanotubes obtained.

[0183] <Catalyst supply mechanism>

[0184] The catalyst supply mechanism 23 may be a mechanism that holds a disintegrable catalyst D in a carbon-containing gas flow, and when subjected to the wind pressure of the carbon-containing gas, the disintegrable catalyst D disintegrates and is divided into a plurality of catalyst particles P. The catalyst supply mechanism 23 may be a mechanism that holds a long-sized disintegrable catalyst D in the form of a belt or a rod, for example, and gradually feeds the disintegrable catalyst D into the reaction chamber 21. By using the disintegrable catalyst D in this way, a plurality of catalyst particles P in a contact state can be formed at a high temperature in a carbon-containing gas flow, which makes it possible to reliably grow carbon nanotubes between the plurality of catalyst particles.

[0185] As the disintegrable catalyst D, a metal foil that can be easily formed into fine catalyst particles P is suitably used. Examples of the material for the disintegrable catalyst D may include iron, nickel, etc., and particularly preferably high-purity iron having excellent disintegrability and catalytic properties. It is believed that when high-purity iron is heated to a high temperature in the reaction chamber 21 and exposed to a carbon-containing gas, iron carbide (Fe 2 O 2 ) is formed on its surface due to carburization. 3 C), whereby the high-purity iron is easily disintegrated from the surface and the catalyst fine particles P can be sequentially released. In this case, the main component of the catalyst particles P formed is iron carbide or iron oxide (Fe 2 O 3 ).

[0186] The lower limit of the average diameter of the catalyst particles P finally captured by the substrate B is preferably 30 nm, more preferably 40 nm, and further preferably 50 nm. On the other hand, the upper limit of the average diameter of the catalyst particles P captured by the substrate B is preferably 1000 μm, more preferably 100 μm, and further preferably 10 μm. If the average diameter of the catalyst particles P captured by the substrate B is less than the lower limit, the diameter of the carbon nanotubes formed by the catalyst particles is small and the elongation is small, which may not be able to fully extend the carbon nanotubes. On the contrary, if the average diameter of the catalyst particles captured by the substrate is greater than the upper limit, the carbon nanotubes formed from the catalyst particles may be difficult to extend.

[0187] The lower limit of the average thickness of the metal foil used as the disintegrable catalyst D is preferably 1 μm, and more preferably 2 μm. On the other hand, the upper limit of the average thickness of the metal foil used as the disintegrable catalyst D is preferably 500 μm, and more preferably 200 μm. If the average thickness of the metal foil used as the disintegrable catalyst D is less than the lower limit, the metal foil may be broken and blown away by the carbon-containing gas. On the contrary, if the average thickness of the metal foil used as the disintegrable catalyst D is greater than the upper limit, the disintegration speed may be slow, which may reduce the formation efficiency of carbon nanotubes.

[0188] <Substrate Holding Mechanism>

[0189] The substrate holding mechanism 24 holds the substrate B below the catalyst supply position of the catalyst supply mechanism 23 so that the substrate B extends downstream along the flow direction of the carbon-containing gas. Considering the falling speed of the catalyst particles P in the carbon-containing gas flow, it is preferred that the substrate B is held to extend widely within the range on which the catalyst particles P may fall.

[0190] The substrate holding mechanism 24 causes the substrate B to capture the catalyst particles P released by the catalyst supply mechanism 23, and holds the catalyst particles P at the captured position against the flow of the carbon-containing gas. Therefore, due to the wind pressure of the carbon-containing gas applied to the carbon nanotube extending from the catalyst particles P held on the substrate B and to the other catalyst particles P located at the other end of the carbon nanotube, the carbon nanotube extending from the catalyst particles P held on the substrate B is pulled to be plastically deformed, and the carbon nanotube is extended in the longitudinal direction while the diameter of the carbon nanotube is reduced.

[0191] Even during the extension of the carbon nanotubes in this manner, carbon nanotubes having the original diameter are grown on the catalyst particles P. Therefore, Figure 6 As shown, the carbon nanotube produced by the FB method using the carbon nanotube production apparatus 20 may include a tubular tube portion T and a conical cone portion C whose diameter continuously increases from the end of the tube portion.

[0192] That is, the carbon nanotube manufacturing device 20 forms the carbon nanotubes by the vapor phase growth method, and at the same time, uses the wind pressure of the carbon-containing gas to extend the carbon nanotubes, thereby converting a part of the hexagonal unit cells of the carbon nanotubes into pentagonal unit cells, thereby forming a conical cone portion, and converting the pentagonal unit cells into hexagonal unit cells again, thereby forming a tube portion, which is a carbon nanotube with a smaller diameter.

[0193] Since the carbon nanotube manufacturing apparatus 20 extends the carbon nanotubes grown on the catalyst particles P, the carbon nanotube manufacturing apparatus 20 can form the tube portion at a very fast speed compared to the growth speed of the carbon nanotubes on the catalyst particles P, which makes it possible to form longer carbon nanotubes in a relatively short time. Therefore, even if the conditions for continuously growing carbon nanotubes on the catalyst particles P can be maintained for a short time, sufficiently long carbon nanotubes can be formed.

[0194] It is believed that the carbon nanotube manufacturing apparatus 20 promotes the introduction of carbon atoms at the growth points of the carbon nanotubes by applying tension to the carbon nanotubes on the catalyst particles P using the wind pressure of the carbon-containing gas. As a result, it is believed that the carbon nanotube manufacturing apparatus 20 can further increase the growth rate of the carbon nanotubes, thereby increasing the increase rate of the length of the obtained carbon nanotubes.

[0195] It is considered that in the carbon nanotube production apparatus 20, by applying tension to the carbon nanotubes on the catalyst particles P using the wind pressure of the carbon-containing gas, the carbon nanotubes are not easily bent, and thus a straight carbon nanotube including a tube portion T composed only of a six-membered ring of carbon can be obtained. Even when the carbon nanotube composed only of a six-membered ring of carbon is exposed to a high-temperature oxidizing gas (atmosphere) in the third step of the third embodiment described below, it is not easily deteriorated, and thus the quality can be maintained.

[0196] On the other hand, if the carbon nanotube contains a five-membered ring or a seven-membered ring of carbon in addition to a six-membered ring of carbon, it is likely that a bend originating from the five-membered ring or the seven-membered ring will be generated. When the carbon nanotube containing a bend is exposed to a high-temperature oxidizing gas (atmosphere) in the third step of the third embodiment described below, a hole is formed in the bend portion because the reaction proceeds faster, and because a dangling bond is formed, the bend portion is degraded, resulting in quality degradation. In such a carbon nanotube with degraded quality, a strong D band peak is confirmed in Raman spectroscopy analysis.

[0197] As the substrate B, for example, a silicon substrate, a heat-resistant glass substrate made of, for example, quartz glass, a ceramic substrate made of, for example, alumina, etc. can be used. In addition, the substrate holding mechanism 24 can move a long-sized substrate or a plurality of substrates along the flow direction of the carbon-containing gas. By moving the substrate B in this way, the carbon nanotube manufacturing apparatus can prevent the catalyst particles P from filling up the surface of the substrate B, and can continuously manufacture carbon nanotubes.

[0198] (Step 2)

[0199] In the second step, a plurality of carbon nanotube composites are obtained by coating each of the plurality of carbon nanotubes prepared in the first step with a layer containing amorphous carbon.

[0200] In the conventional manufacturing method of carbon nanotubes, byproducts such as amorphous carbon and graphite crystallites may be formed while the carbon nanotubes are being produced. Since these byproducts affect the conductivity and mechanical properties of the carbon nanotubes themselves, the initial properties of the carbon nanotubes such as conductivity and mechanical properties are deteriorated. Therefore, for conventional carbon nanotubes, in order to improve the crystallinity of the carbon nanotubes, a technology for removing byproducts such as amorphous carbon and graphite crystallites has been studied.

[0201] A method for producing carbon nanotubes has also been studied, in which byproducts such as amorphous carbon are not formed during the production process of the carbon nanotubes, and highly crystalline carbon nanotubes can be obtained. However, since highly crystalline carbon nanotubes are very small, with a diameter of about 0.8 nm to 10 nm, the carbon nanotubes cannot be observed with an optical microscope. Therefore, it is difficult to handle the carbon nanotubes.

[0202] Therefore, by earnestly studying a method that helps to make the handling of highly crystalline carbon nanotubes easy, the present inventors have recently found that by coating carbon nanotubes with a layer containing amorphous carbon to increase the diameter, the carbon nanotubes can be observed with an optical microscope and easily handled. The means of forming a carbon nanotube composite by coating highly crystalline carbon nanotubes with a layer containing amorphous carbon is based on a technical concept that is completely opposite to the conventional technical concept of removing by-products such as amorphous carbon and graphite crystallites contained in carbon nanotubes.

[0203] An example of a method for coating carbon nanotubes with a layer containing amorphous carbon includes heat-treating the carbon nanotubes at a temperature of 950°C to 1100°C in a hydrocarbon gas. Examples of hydrocarbon gases that can be used include methane gas, ethylene gas, acetylene gas, ethanol gas, and benzene gas. The temperature of the heat treatment is preferably 950°C to 1050°C. The duration of the heat treatment is appropriately changed according to the temperature of the heat treatment and the target thickness of the layer containing amorphous carbon. For example, the duration of the heat treatment is preferably 1 minute to 60 minutes, and more preferably 5 minutes to 30 minutes.

[0204] The total concentration of methane gas, ethylene gas, acetylene gas, ethanol gas and benzene gas in the hydrocarbon gas is preferably 1% by volume or more, more preferably 70% by volume or more, and further preferably 100% by volume or more. If the total concentration is less than 1% by volume, the formation speed of the layer containing amorphous carbon may be slowed down. On the other hand, the upper limit of the total concentration is not particularly limited, and is preferably 100% by volume from the viewpoint of increasing the formation speed of the layer containing amorphous carbon. In addition to methane gas, ethylene gas, acetylene gas, ethanol gas and benzene gas, the hydrocarbon gas may also include an inert gas such as helium, argon or nitrogen that does not promote oxidation of the layer containing amorphous carbon, and / or a reducing gas such as hydrogen.

[0205] The average flow rate of the hydrocarbon gas in the reaction chamber is preferably 0.05 cm / sec or more, more preferably 0.10 cm / sec or more, and further preferably 0.20 cm / sec or more. If the average flow rate of the hydrocarbon gas is less than 0.05 cm / sec, the formation rate of the layer containing amorphous carbon may be significantly reduced. On the other hand, the upper limit of the average flow rate of the hydrocarbon gas in the reaction chamber is preferably 10.0 cm / sec or less, more preferably 1 cm / sec or less, and further preferably 0.50 cm / sec or less. If the average flow rate of the hydrocarbon gas exceeds 10.0 cm / sec, the hydrocarbon gas may pass through the reaction chamber before reaching the thermal decomposition temperature of the hydrocarbon gas, and a layer containing amorphous carbon may not be formed.

[0206] Each carbon nanotube composite obtained in the second step has a large diameter, can be observed with an optical microscope, and is easy to handle.

[0207] (Third step)

[0208] In the third step, the plurality of carbon nanotube composites prepared in the second step are oriented and assembled along the longitudinal direction thereof, thereby obtaining a carbon nanotube composite aggregate line. The expression "a plurality of carbon nanotube composites are oriented and assembled along the longitudinal direction thereof" means that a plurality of carbon nanotube composites are arranged and assembled so that the longitudinal directions of the respective plurality of carbon nanotube composites extend in substantially the same direction. It should be noted that the expression "substantially the same direction" means that the maximum angle formed between two different carbon nanotube composites included in the carbon nanotube composite aggregate line is -10° or less.

[0209] The method for assembling a plurality of carbon nanotube composites is not particularly limited, as long as it is any method that can orient and assemble the carbon nanotube composites in their longitudinal direction. Examples of methods that can be used include: a method of placing each carbon nanotube composite one by one so that it is arranged in a predetermined direction to obtain a carbon nanotube composite assembly line; a method of dispersing the carbon nanotube composite in a liquid phase or a gas phase and then flowing the liquid phase or the gas phase in a constant direction to obtain a CNT composite assembly line; a method of dry spinning a carbon nanotube composite oriented vertically to the surface of a substrate; and an electrospinning method, etc. In particular, from the viewpoint of easy operation, a method using a liquid phase is preferred.

[0210] When a liquid phase is used for the method of gathering multiple carbon nanotube complexes, the third step preferably includes: a third step a of obtaining a carbon nanotube complex dispersion by dispersing multiple carbon nanotube complexes in a solvent; a third step b of orienting multiple carbon nanotube complexes in a specific direction by causing the carbon nanotube complex dispersion to flow in a specific direction; and a third step c of obtaining a carbon nanotube complex assembly line by removing the solvent in the carbon nanotube complex dispersion after the third step b.

[0211] In the third step a, examples of the solvent that can be used include methanol, ethanol, propanol, toluene, 1,2-dichloroethane, 1,2-dichlorobenzene, o-dichlorobenzene, carbon disulfide, dimethyl sulfoxide, N,N-dimethylformamide, and pure water.

[0212] In the third step b, an example of a method for causing the carbon nanotube composite dispersion to flow in a specific direction includes a method in which a substrate including grooves formed in a specific direction is prepared, and the carbon nanotube composite dispersion is caused to flow from one direction of the grooves of the substrate in the longitudinal direction of the grooves of the substrate. Thus, the longitudinal directions of the plurality of carbon nanotube composites in the carbon nanotube composite dispersion are oriented in the longitudinal direction of the grooves of the substrate.

[0213] When the carbon nanotube composite dispersion liquid is allowed to flow through the groove, the flow rate of the carbon nanotube composite dispersion liquid is preferably adjusted so that the carbon nanotube composite dispersion liquid does not flow out of the groove.

[0214] Examples of substrates that can be used include quartz substrates, silicon, silicon dioxide, aluminum oxide, and silicon nitride.

[0215] The size of the groove of the substrate can be appropriately selected according to the purpose of the heat-treated body of the carbon nanotube composite wire assembly. For example, the width of the groove in the surface of the substrate is preferably 100 μm to 1000 μm, and the maximum depth of the groove from the surface of the substrate is preferably 50 μm to 500 μm.

[0216] In the third step c, examples of methods for removing the solvent in the carbon nanotube composite dispersion include methods of evaporating the solvent by natural evaporation or heating. When the solvent is evaporated by heating, the heating temperature is preferably set to a boiling point or above of the solvent. Thus, a carbon nanotube composite aggregate wire can be obtained.

[0217] [Fourth Embodiment: Method for Manufacturing Heat-treated Carbon Nanotube Composite Wire Assembly]

[0218] The method for manufacturing a heat-treated body of a carbon nanotube composite aggregate wire according to the present embodiment includes: a first step of preparing a plurality of carbon nanotubes; a second step of obtaining a plurality of carbon nanotube composites by coating each of the plurality of carbon nanotubes with a layer containing amorphous carbon; a third step of obtaining a carbon nanotube composite aggregate wire by orienting and aggregating the plurality of carbon nanotube composites along their longitudinal direction; and a fourth step of obtaining a heat-treated body of the carbon nanotube composite aggregate wire by heat-treating the carbon nanotube composite aggregate wire to remove the layer containing amorphous carbon.

[0219] (Step 1, Step 2, and Step 3)

[0220] The first step, the second step, and the third step may be the same as the first step, the second step, and the third step described in the third embodiment, respectively.

[0221] (Step 4)

[0222] In the fourth step, the carbon nanotube composite wire assembly obtained in the third step is heat-treated to remove the layer containing amorphous carbon, thereby obtaining a heat-treated body of the carbon nanotube composite wire assembly.

[0223] Through in-depth research on the method of removing the layer containing amorphous carbon in the carbon nanotube composite assembly line, the inventors found that by heat treating the carbon nanotube composite under specified conditions, only the layer containing amorphous carbon in the carbon nanotube composite assembly line can be removed while maintaining the crystallinity of the carbon nanotubes, and thereby a heat-treated body of the carbon nanotube composite assembly line with high crystallinity can be obtained.

[0224] Examples of heat treatment include heat treating the carbon nanotube composite wires at a temperature of 400° C. to 800° C. under oxidizing conditions. This can remove only the layer containing amorphous carbon in the carbon nanotube composite wires while maintaining high crystallinity of the carbon nanotubes.

[0225] If the temperature of the heat treatment is less than 400° C., it is not possible to sufficiently remove the layer containing amorphous carbon. On the other hand, if the temperature of the heat treatment exceeds 800° C., the carbon nanotubes may burn and disappear. The temperature of the heat treatment is preferably 420° C. to 750° C., more preferably 560° C. to 690° C., and further preferably 550° C. to 650° C.

[0226] The duration of the heat treatment is appropriately changed depending on the temperature of the heat treatment and the thickness of the layer containing amorphous carbon. For example, the time of the heat treatment is preferably from 1 minute to 120 minutes, and more preferably from 10 minutes to 60 minutes.

[0227] The D / G ratio of the heat-treated body of the carbon nanotube composite wire assembly obtained in the fourth step is preferably 0.1 or less, and the D / G ratio is the ratio of the peak intensity of the D band to the peak intensity of the G band in the Raman spectrum analysis with a wavelength of 532nm. Thus, the heat-treated body of the carbon nanotube composite wire assembly can have high crystallinity. Therefore, the heat-treated body of the carbon nanotube composite wire assembly can have high tensile strength and high conductivity. The D / G ratio is further preferably 0.01 or less. Although the lower limit of the D / G ratio is not particularly limited, it can be (for example) 0.001 or more.

[0228] When the diameter of the carbon nanotube composite wire assembly obtained in the third step is P1, and the diameter of the heat-treated body of the carbon nanotube composite wire assembly obtained in the fourth step is P2, P1 and P2 preferably show a relationship represented by the following Formula 1:

[0229] 100≤P1 / P2≤10000 Formula 1.

[0230] In the case where P1 and P2 show a relationship represented by the above formula 1, this situation indicates that the layer containing amorphous carbon in the carbon nanotube composite assembly wire is fully removed, and in the heat-treated body of the carbon nanotube composite assembly wire, a plurality of refined carbon nanotubes are in contact with or aggregated with each other. Thus, the heat-treated body of the carbon nanotube composite assembly wire can have excellent electrical conductivity. It should be noted that the heat-treated body of the CNT composite assembly wire can be directly observed using a transmission electron microscope to confirm the manner in which a plurality of refined CNTs in the heat-treated body of the CNT composite assembly wire are in contact with or aggregated with each other. In addition, in such a heat-treated body, it can be confirmed by X-ray diffraction that the CNT composite assembly wire is regularly arranged.

[0231] When the D / G ratio of each carbon nanotube prepared in the first step is R1, and the D / G ratio of the heat-treated carbon nanotube composite wire assembly obtained in the fourth step is R2, R1 and R2 preferably show a relationship represented by the following formula 2:

[0232] -0.2≤(R2-R1)≤0.2 Formula 2

[0233] (In the above formula 2, R1 satisfies 0≤R1≤0.2, and R2 satisfies 0≤R2≤0.2).

[0234] When R1 and R2 show the relationship represented by the above formula 2, this means that a heat-treated body of the carbon nanotube composite aggregate wires with high crystallinity is obtained by the fourth step without deteriorating the carbon nanotubes in the carbon nanotube composite.

[0235] R1 and R2 further preferably exhibit a relationship represented by the following formula 3 or 4:

[0236] -0.1≤(R2-R1)≤0.1 Formula 3

[0237] (In the above formula 3, R1 satisfies 0≤R1≤0.2, and R2 satisfies 0≤R2≤0.2)

[0238] R1=R2 Formula 4

[0239] (In the above formula 4, R1 satisfies 0≤R1≤0.2, and R2 satisfies 0≤R2≤0.2).

[0240] Example

[0241] The first to fourth embodiments will be described in more detail with reference to examples. However, the present embodiment is not limited to these examples.

[0242] <Sample 1>

[0243] (Preparation of Carbon Nanotubes)

[0244] use Figure 8 The carbon nanotube manufacturing apparatus 20 shown makes carbon nanotubes. A quartz tube with an inner diameter of 20 mm is set in a heating furnace, and a substrate with a width of 10 mm and a square pure iron sheet (purity: 4N) with a side length of 1 cm and a thickness of 10 μm as a disintegrable catalyst are placed in the quartz tube. Then, while argon gas with an argon concentration of 100 volume % is supplied to the quartz tube at a rate of 60 cc / min, the temperature in the heating furnace is raised to 1000° C. Then, in addition to argon gas, methane gas is supplied at a rate of 3000 cc / min for 15 seconds, and then the flow rate (speed) is changed to less than 3000 cc / min and the supply is continued for one hour.

[0245] Due to the supply of methane gas, the pure iron sheet disintegrated and released catalyst particles, and catalyst particles with a particle size of 30nm to 300nm were attached to the substrate. When the substrate was taken out of the quartz tube and observed with a scanning electron microscope, carbon nanotubes were formed between some of the catalyst fine particles attached to the substrate in a manner of bridging between the particles.

[0246] The diameter of the obtained carbon nanotubes was measured by Raman spectroscopy analysis, and the length was measured by observation with a scanning electron microscope. The carbon nanotubes had a diameter of 1 nm to 10 nm, and a length of 1 μm to 3 cm.

[0247] The structure of one of the carbon nanotubes identified above was confirmed using a transmission electron microscope. It was confirmed that the carbon nanotube was a double-walled carbon nanotube that had a straight overall appearance and had conical portions at both ends.

[0248] The carbon nanotubes are subjected to Raman spectroscopy analysis to obtain a Raman spectrum. The measurement conditions of the Raman spectroscopy analysis are as described in the first embodiment. When the D / G ratio is calculated from the peak intensity of the D band and the peak intensity of the G band in the Raman spectrum, the D / G ratio is 0.

[0249] (Production of Carbon Nanotube Composite)

[0250] Next, the substrate on which the carbon nanotubes were attached was placed in a quartz tube, and while methane gas having a methane gas concentration of 100% by volume was supplied into the quartz tube at a rate of 0.10 cm / sec, the temperature in the heating furnace was maintained at 1050° C. for 30 minutes, thereby heat-treating the carbon nanotubes. Thus, a layer containing amorphous carbon was formed around each carbon nanotube to obtain a carbon nanotube composite.

[0251] The carbon nanotube composite obtained above was observed with a transmission electron microscope and an optical microscope to measure its diameter and length. The diameter of the CNT composite was 0.1 μm to 2 μm, and the length was 10 μm to 3 cm.

[0252] The structure of the carbon nanotube composite was examined using a transmission electron microscope. As a result, it was confirmed that the carbon nanotube composite was fibrous and had a linear shape as a whole, and a layer containing amorphous carbon was formed on the surface of each carbon nanotube.

[0253] The carbon nanotube composite obtained as described above can be picked up with tweezers under observation of an optical microscope and placed at a predetermined position. That is, the carbon nanotube composite has good handling properties.

[0254] The carbon nanotube composite obtained above was subjected to Raman spectroscopy analysis to obtain a Raman spectrum. The measurement conditions of the Raman spectroscopy analysis were as described in the first embodiment. When the D / G ratio was calculated from the peak intensity of the D band and the peak intensity of the G band in the Raman spectrum, the D / G ratio was 0.7.

[0255] (Fabrication of Carbon Nanotube Composite Wires)

[0256] A carbon nanotube composite dispersion was obtained by dispersing 100 μg of the carbon nanotube composite obtained above in 1 ml of a 99.5% ethanol solution.

[0257] A quartz substrate including grooves formed in its surface was prepared. The dimensions of the grooves were as follows: the width of the grooves in the surface of the quartz substrate was 300 μm, the maximum depth of the grooves from the surface of the quartz substrate was 200 μm, and the cross-sectional shape perpendicular to the longitudinal direction of the grooves was semicircular.

[0258] The carbon nanotube composite dispersion is caused to flow along the longitudinal direction of the groove from one direction of the groove, so that the longitudinal directions of the plurality of carbon nanotube composites in the carbon nanotube composite dispersion are aligned along the longitudinal direction of the groove of the substrate.

[0259] When the obtained carbon nanotube composite aggregate line was observed with an optical microscope, it was confirmed that a plurality of carbon nanotube composites were oriented in the longitudinal direction of the carbon nanotube composite aggregate line.

[0260] The carbon nanotube composite aggregate wire obtained above was observed with an optical microscope to measure its diameter and length. The diameter (P1) of the CNT composite aggregate wire was 300 μm, and the length was 10 mm.

[0261] Based on the above description, the CNT composite aggregate wire of Sample 1 corresponds to the embodiment.

[0262] (Preparation of Heat-treated Carbon Nanotube Composite Wire Aggregate)

[0263] Next, the carbon nanotube composite aggregate wire obtained above was heat-treated in the atmosphere at a temperature of 650° C. for 60 minutes to obtain a heat-treated carbon nanotube composite aggregate wire body.

[0264] When the heat-treated body of the CNT composite wire assembly of Sample 1 was examined with a scanning electron microscope, it was confirmed that a plurality of refined carbon nanotubes were oriented and assembled in the longitudinal direction of the heat-treated body of the CNT composite wire assembly.

[0265] The heat-treated body of the CNT composite wire assembly of Sample 1 was observed with a scanning electron microscope to measure its diameter. The diameter (P2) of the heat-treated body of the CNT composite wire assembly was 50 nm.

[0266] When the value of P1 / P2 was calculated from the diameter P1 of the carbon nanotube composite wire assembly and the diameter P2 of the heat-treated body of the carbon nanotube composite wire assembly, the value of P1 / P2 was 6,000.

[0267] Raman spectroscopy analysis was performed on the heat-treated body of the carbon nanotube composite wire assembly in a state of being placed on a quartz substrate to produce a Raman imaging image of the G band (see Figure 6 ) and D-band Raman imaging images (see Figure 7 ). The measurement conditions of the Raman spectroscopy analysis are as described in the first embodiment, and the method of generating each Raman imaging image is as described in the second embodiment.

[0268] Depend on Figure 6 and Figure 7 The Raman imaging image shown can confirm that the heat-treated body of the CNT composite wire assembly of sample 1 exists in the portion surrounded by the dotted line, and in the heat-treated body of the CNT composite wire assembly, highly crystalline refined carbon nanotubes exist, and there is no layer containing amorphous carbon.

[0269] The heat-treated body of the obtained CNT composite wire assembly is subjected to Raman spectroscopy analysis to obtain a Raman spectrum. The measurement conditions of the Raman spectroscopy analysis are as described in the first embodiment. When the D / G ratio is calculated from the peak intensity of the D band and the peak intensity of the G band in the Raman spectrum, the D / G ratio is 0.

[0270] The value of the D / G ratio of the carbon nanotubes (R1) and the value of the D / G ratio of the heat-treated body of the CNT composite wire assembly (R2) are both 0, that is, these values ​​satisfy R1=R2.

[0271] Based on the above description, the heat-treated body of the CNT composite aggregate wire of Sample 1 corresponds to the Example.

[0272]

[0273] <Samples 2 to 4>

[0274] In each of Samples 2 to 4, carbon nanotubes were prepared by the same method as Sample 1. The diameter, length, and D / G ratio (R1) of the obtained carbon nanotubes were measured by the same method as Sample 1. The results are shown in the "Diameter", "Length", and "D / G ratio (R1)" columns of the "CNT" column in Table 1.

[0275] Each of the obtained carbon nanotubes was heat treated in a hydrocarbon gas to obtain a carbon nanotube composite in the same manner as Sample 1. The temperature and time of the heat treatment are shown in the "Temperature" and "Time" columns of the "Second Step" column in Table 1.

[0276] The diameter, length and D / G ratio of the obtained carbon nanotube composite were measured by the same method as Sample 1. The results are shown in the "Diameter", "Length" and "D / G Ratio" columns of the "CNT Composite" column in Table 1.

[0277] The structure of each carbon nanotube composite of Samples 2 to 4 was examined with a transmission electron microscope. The results confirmed that each carbon nanotube composite was fibrous and had a linear shape as a whole, and a layer containing amorphous carbon was formed on the surface of one carbon nanotube.

[0278] The carbon nanotube composites of each of Samples 2 to 4 were picked up with tweezers and placed at a predetermined position under observation of an optical microscope. That is, each carbon nanotube composite had good handling properties.

[0279] Next, using the carbon nanotube composites of each of Samples 2 to 4, a carbon nanotube composite aggregate wire was prepared by the same method as Sample 1.

[0280] When the carbon nanotube composite aggregate line of each of Samples 2 to 4 was observed with an optical microscope, it was confirmed that a plurality of carbon nanotube composites were aligned in the longitudinal direction of the carbon nanotube composite aggregate line.

[0281] The diameter P1 and length of each of the carbon nanotube composite aggregate wires of Samples 2 to 4 were measured by the same method as Sample 1. The results are shown in the "Diameter P1" and "Length" columns of the "CNT composite aggregate wire" column of Table 1. Based on these results, each of the CNT composite aggregate wires of Samples 2 to 4 corresponds to the Example.

[0282] Next, the carbon nanotube composite wire assemblies of each of Samples 2 to 4 were heat-treated in the atmosphere. The temperature and time of the heat treatment are shown in the "Temperature" and "Time" columns of the "Fourth Step" column in Table 1.

[0283] When Sample 2 was observed with a transmission electron microscope after the heat treatment, the carbon nanotube composite assembly line did not change, and a layer containing amorphous carbon on the surface of the carbon nanotube was confirmed. Therefore, it was confirmed that the layer containing amorphous carbon could not be removed under the heat treatment conditions of Sample 2. The reason why the layer containing amorphous carbon could not be removed may be that the heat treatment time was short.

[0284] When Sample 3 was observed with a transmission electron microscope after the heat treatment, a layer containing amorphous carbon on the surface of the carbon nanotube was confirmed, but the amount of the layer containing amorphous carbon was reduced. Therefore, it was confirmed that the layer containing amorphous carbon could not be sufficiently removed under the heat treatment conditions of Sample 3. The reason why the layer containing amorphous carbon could not be sufficiently removed may be that the heat treatment time was short.

[0285] When sample 4 was observed with a transmission electron microscope after the heat treatment, neither the carbon nanotubes nor the layer containing amorphous carbon could be observed. Therefore, it was confirmed that the carbon nanotubes also disappeared together with the layer containing amorphous carbon under the heat treatment conditions of sample 4. The reason why the carbon nanotubes disappeared together with the layer containing amorphous carbon may be that the heat treatment time was long.

[0286] For the heat-treated bodies of the carbon nanotube composite wire assemblies of each of Samples 2 and 3, the diameter and D / G ratio (R2) were measured by the same method as Sample 1. In addition, the values ​​of (R2-R1) and P1 / P2 were calculated. The results are shown in the "Diameter P2" and "D / G ratio" columns and the "(R2-R1)" and "P1 / P2" columns of the "Heat-treated body of CNT composite wire assemblies" column in Table 1.

[0287] Although the embodiments and examples of the present disclosure have been described above, it is originally intended to appropriately combine or variously modify the features of the embodiments and examples.

[0288] It should be understood that the embodiments and examples disclosed herein are illustrative and non-restrictive in all aspects. The scope of the present invention is limited by the scope of the claims, rather than by the embodiments and examples described above, and the scope of the present invention is intended to include any modification within the scope and meaning equivalent to the scope of the claims.

[0289] Reference numerals list

[0290] 1: carbon nanotube complex; 2: carbon nanotube; 3: amorphous carbon; 10: carbon nanotube complex assembly line; 20: carbon nanotube manufacturing device; 21: reaction chamber; 22: gas supply mechanism; 23: catalyst supply mechanism; 24: substrate holding mechanism; 25: inlet area; 26: formation area; 27: heater; 28: gas tank; 29: flow control valve; C: cone; D: degradable catalyst; P: catalyst particles.

Claims

1. A method for manufacturing a heat-treated body of a carbon nanotube composite wire assembly, the method comprising: A first step of preparing a plurality of carbon nanotubes; a second step of obtaining a plurality of carbon nanotube composites by coating each of the plurality of carbon nanotubes with a layer containing amorphous carbon; a third step of obtaining a carbon nanotube composite aggregate line by aligning and assembling the plurality of carbon nanotube composites along their longitudinal direction; as well as A fourth step is to obtain a heat-treated body of the carbon nanotube composite wire assembly by heat-treating the carbon nanotube composite wire assembly to remove the layer containing amorphous carbon.

2. The method for producing a heat-treated body of a carbon nanotube composite wire assembly according to claim 1, wherein The carbon nanotube has a D / G ratio of 0.1 or less, wherein the D / G ratio is a ratio of the peak intensity of the D band to the peak intensity of the G band in Raman spectroscopy analysis at a wavelength of 532 nm, and Each of the plurality of carbon nanotube composites is in a fiber shape and has a diameter of 0.1 μm to 50 μm.

3. The method for producing a heat-treated body of a carbon nanotube composite wire assembly according to claim 1 or 2, wherein When the diameter of the carbon nanotube composite wire assembly is P1, and the diameter of the heat-treated body of the carbon nanotube composite wire assembly is P2, P1 and P2 show a relationship represented by the following formula 1: 100≤P1 / P2≤10000 Formula 1.

4. The method for producing a heat-treated carbon nanotube composite wire assembly according to claim 1 or 2, wherein the second step comprises heat-treating the plurality of carbon nanotubes at a temperature of 950°C to 1100°C in a hydrocarbon-based gas.

5. The method for producing a heat-treated body of a carbon nanotube composite wire assembly according to claim 1 or 2, wherein The third step includes The third step (a) is to obtain a carbon nanotube composite dispersion by dispersing the plurality of carbon nanotube composites in a solvent, a third step (b) of orienting the plurality of carbon nanotube composites in a specific direction by causing the carbon nanotube composite dispersion to flow in the specific direction, and After the third step (b), a third step (c) of obtaining the carbon nanotube composite aggregate wire is performed by removing the solvent in the carbon nanotube composite dispersion liquid.

6. The method for manufacturing a heat-treated body of a carbon nanotube composite wire assembly according to claim 1 or 2, wherein the heat treatment in the fourth step comprises heat-treating the carbon nanotube composite wire assembly at a temperature of 400°C to 800°C under oxidizing conditions.

7. The method for manufacturing a heat-treated body of a carbon nanotube composite wire assembly according to claim 6, wherein the heat treatment in the fourth step comprises heat-treating the carbon nanotube composite wire assembly at a temperature of 560°C to 690°C under an oxidizing condition.

Citation Information

Patent Citations

  • Method for manufacturing carbon nano-structure

    JP2005330175A

  • Cleaning device and cleaning method

    JP2018164909A

  • Composite fiber comprising wholly aromatic polyamide and carbon nanotube

    CN1720295A

  • Carbon nanotube and method for producing the same

    JP2003146634A

  • Carbon nanotube and process for producing the same

    US20080063586A1